HAK ASASI BERAGAMA PERSPEKTIF FILSAFAT ONTOLOGI PANCASILA DALAM KERANGKA NEGARA HUKUM - Dede Yuda Wahyu Nurhuda; Fadil Ahmad Junaedi; Jeffri Nugraha (CV Widina Media Utama, 2026)
ABSTRACTIndonesia is a nation rich in ethnic, cultural, and religious diversity that has coexisted since the Nusantara era. Following independence, religious values were officially accommodated by the country's founders, who affirmed that Indonesia is a religious nation, although it is not a religious state. As a state governed by law (negara hukum) as regulated in Article 1 Paragraph (3) of the 1945 Constitution, Indonesia is obligated to provide legal protection for human rights, including the right to freedom of religion and worship. In reality, however, social friction resulting from differences in beliefs and past human rights violations involving state apparatus still pose challenges to national life. This study aims to examine the alignment of the principles of the human right to religion from the perspective of the ontological philosophy of Pancasila within the framework of the Indonesian legal state. The research method employed is a normative (doctrinal) legal research method with a descriptive-analytical nature. Legal materials were collected through library research and internet-based legal document searches. The analysis was conducted descriptively, qualitatively, and normatively using deductive reasoning, along with a statute approach and a conceptual approach. The results indicate that ontologically, the fundamental essence of Pancasila is the human being as the primary legal subject, characterized by a monopluralis nature (possessing a balanced structure, nature, and status of existence as an individual, social being, and creation of God). As the staatsfundamentalnorm (fundamental norm of the state), Pancasila serves as the primary source of validity and the direction for formulating national laws, giving rise to the concept of the